The role of entry screening in case finding of tuberculosis among asylum seekers in Norway - Helvik Anne-Sofie; Vahedi Saeed; Winje Brita A; Heldal Einar; Jacobsen Geir W; Harstad Ingunn; Steinshamn Sigurd L; Garåsen Helge (BMC, 2010)
Abstract Background Most new cases of active tuberculosis in Norway are presently caused by imported strains and not transmission within the country. Screening for tuberculosis with a Mantoux test of everybody and a chest X-ray of those above 15 years of age is compulsory on arrival for asylum seekers. We aimed to assess the effectiveness of entry screening of a cohort of asylum seekers. Cases detected by screening were compared with cases detected later. Further we have characterized cases with active tuberculosis. Methods All asylum seekers who arrived at the National Reception Centre between January 2005 - June 2006 with an abnormal chest X-ray or a Mantoux test ≥ 6 mm were included in the study and followed through the health care system. They were matched with the National Tuberculosis Register by the end of May 2008. Cases reported within two months after arrival were defined as being detected by screening. Results Of 4643 eligible asylum seekers, 2237 were included in the study. Altogether 2077 persons had a Mantoux ≥ 6 mm and 314 had an abnormal chest X-ray. Of 28 cases with tuberculosis, 15 were detected by screening, and 13 at 4-27 months after arrival. Abnormal X-rays on arrival were more prevalent among those detected by screening. Female gender and Somalian origin increased the risk for active TB. Conclusion In spite of an imperfect follow-up of screening results, a reasonable number of TB cases was identified by the programme, with a predominance of pulmonary TB.